PENGARUH TEPUNG LIMBAH RUMPUT LAUT PADA RANSUM PAKAN TERHADAP PERTUMBUHAN, FEED CONVERTION RATIO DAN SURVIVAL RATE IKAN NILA MERAH (Oreochromis sp.) - Kwen, Anastasia Delviana; Nuhman (FISHERIES Jurnal Perikanan dan Ilmu Kelautan, 2021)
This study aims to determine the effect of the addition of seaweed waste flour to feed ration on growth, Feed Convertion Ratio (FCR), and Survival Rate (SR) of red tilapia (Oreochromis sp.). The method used is an experimental method with a Completely Randomized Design (CRD) with 4 treatments and 6 replications with a composition of different treatment additives bran and flour seaweed waste A (0%), B (1: 1), C (2: 1), D (1: 2). Test animals used were red tilapia (Oreochromis sp.) With an average weight of 6-12 grams. Fish kept for 30 days. The results showed that the highest absolute growth was achieved in feed C of 3.15 grams, the highest specific growth rate was achieved in feed A of 1.059%, the best feed conversion ratio was obtained in feed A which was 0.51% and the highest Survival Rate was achieved in feed B amounted to 76.67%.